Lovesick Ellie. 8 - Fujimomo (Kodansha America, Inc, 2023)
Ellie and Ohmi are alone at last--in his room! They are IRL offcial as a couple and Ohmi's every move leaves Ellie breathless and aching for more--and her titillating Twitter posts show it! But the walls go up in moments of intimacy, each reluctant to reveal vulnerabilities. They also have one formidable obstacle to their relationship--Ellie's protectivebut well-meaning dad. Can Ellie convince her dad that she's all grown up and that Ohmi's love is the real deal?